Non-destructive Magnetic Method for the Inspection of Neutron Irradiation Generated Embrittlement of Cladded Nuclear Reactor Pressure Vessel Steel Blocks - Gabor Vertesy; Antal Gasparics; Ildiko Szenthe (Advances and Challenges in Science and Technology Vol. 3, 2023)
Non-destructive inspection of neutron irradiation generated embrittlement of reactor pressure vessel steel is an extremely important task in nuclear industry. The aim of the present study is to suggest and to test experimentally a novel magnetic method, called magnetic adaptive testing (MAT). The influence of neutron irradiation degradation on reactor pressure vessel steel was investigated. Large blocks were irradiated by neutrons at a low irradiation temperature. Samples were measured by MAT method before and after the neutron irradiation. It was shown that the modification of the recorded magnetic parameters due to the neutron irradiation was well detectable by this non-destructive method. It was also shown that the influence of neutron irradiation could be detected with a reasonable signal-to-noise ratio even through the cladding. In both cases (on the cladded side and from the bottom base material) a good, close to linear correlation was found between magnetic parameters and destructively determined ductile to brittle transition temperature. It was also demonstrated, how the base material and the cladding itself can be inspected separately from each other by this non-destructive magnetic measurements. It was found that with the proper choice of the magnetizing yoke dimension, these two different materials could be measured independently of each other. Our results can help for the future practical application of magnetic methods in the regular inspection of nuclear power plants.